Writing Styles and Strategies in Drafting the Statement of Claim - De Mello, Geraldine (2002)
This study examined the generic structure of a legal document, namely, the statement of claim. The writing styles and strategies employed by Malaysian lawyers in the drafting of the statement of claim, particularly pertaining to contracts were also identified whilst looking at the generic structure. Legal writing in English is a branch of English for specific purposes (ESP) particularly in ESL/EFL contexts and as such, theories pertaining to general and ESP writing were looked into. The writing product in most legal writing involves the conventions of the particular genre involved. The first research question looked at why the statement of claim as a legal genre is structured the way it is. The subsequent question aimed at discovering the intricacies and processes that influence the writing styles and strategies employed by lawyers in drafting the statement of claim. The research looked at sentence structures, choice and arrangement of words and sentences, and finally how ideas are conveyed. Finally, the third research question sought to determine whether years of work experience among lawyers in any way influenced their writing styles and strategies. The study sample comprised fifteen lawyers practising in the town of Seremban, Negeri Sembilan, Malaysia. Data collection was via questionnaires, analysis of standard formats of statements of claim, and statements of claim drafted by the sample group. Interviews were also carried out based on semi-structured questions. The findings suggest that firstly the English Language still holds a dominant position in the courts of law, despite the fact that Bahasa Malaysia is the official oral and written language of the court s in the country. Secondly, the statement of claim as a legal genre was found to have a formulaic structure with certain obligatory moves which enable lawyers to identify with them, thus assisting them in drafting their statements of claim effectively, and optional moves that make for some level of creativity, and hence, variation with in the prototype. The writing styles and strategies also varied among the lawyers. In this study, the perceived styles and strategies of the lawyers were discussed. The findings indicate that lawyers follow the recursive nature of writing and do constant revision in the process of drafting in order to produce an effective and yet clear and concise statement of claim. Finally, the findings also reveal that work experience influences the writing styles and strategies of lawyers in their document writing process. It can be concluded then that the significance of this study is to guide and assist lawyers, students and legal practitioners as to the drafting of statements of claim.